Rime volgari in onore di Caterina Vigri (1413- 1463): dal chiostro alla città - Leoni, Juri (Archivum Franciscanum historicum, 2020)
This contribution offers a critical edition of some unpublished poetic verses in the vernacular Italian language in honour of Catherine of Bologna (1413-63).These poems were composed partly by the nuns of the Corpus Christi monastery and partly by literate citizens. This small corpus, to which we can add other rhymes previously published elsewhere by other editors, constitutes an interesting poetic canon that shows the synergy of religious and civil authorities in the hagiographic development of the personality of Catherine Vigri before canonization